Method and device for inspection of hollow machine parts - Kerenyi Istvan (2019)
The subject of the invention relates to a method and a device for inspecting the passage systems of machine components with cavities, especially castings, cylinder heads, for inspecting appropriate flow conductivity, where the passage system comprises at least one inlet opening (2) leading to the surface of the machine component, at least one outlet opening (3) leading to the surface of the machine component, and at least two parallel connected passages (A, B) connecting the inlet opening (2) and the outlet opening (3). A first medium is fed into the passage system through the inlet opening (2) of the passage system, then, with a sharp change a second medium with different physical properties is fed into the passage system, and at the outlet opening (3) of the passage system the change over time of the composition of the medium flowing out is determined, then the composition-time function obtained in this way is compared to the standard composition-time function of a perfect machine component.